a)
( x - 35 ) - 112 = 0
=> x - 35 = 0 + 112 = 112
=> x = 112 + 35 = 147
b)
124 + ( 118 - x ) = 27
=> 124 + 118 - x = 27
=> 242 - x = 27
=> x = 242 - 27 = 215
c)
156 - ( x + 61 ) = 82
=> 156 - x - 61 = 82
=> 95 - x = 82
=> x = 95 - 82 = 13
a) \(\left(x-35\right)-112=0\)
\(\Rightarrow x-35=112\)
\(\Rightarrow x=147\)
b) \(124+\left(118-x\right)=27\)
\(\Rightarrow118-x=-97\)
\(\Rightarrow x=215\)
c) \(156-\left(x+61\right)=82\)
\(\Rightarrow x+61=74\)
\(\Rightarrow x=135\)
a)
( x - 35 ) - 112 = 0
=> x - 35 = 0 + 112 = 112
=> x = 112 + 35 = 147
b 124 + ( 118 - x ) = 27
=> 124 + 118 - x = 27
=> 242 - x = 27
=> x = 242 - 27 = 215
c)
156 - ( x + 61 ) = 82
=> 156 - x - 61 = 82
=> 95 - x = 82
=> x = 95 - 82 = 13
\(a)\left(x-35\right)-112=0\)
\(x-35=112\)
\(x=147\)
\(b)124+\left(118-x\right)=27\)
\(118-x=-97\)
\(x=215\)
\(c)156-\left(x+61\right)=82\)
\(x+61=74\)
\(x=135\)